Negotiating Religious Moderation and Legal Pluralism in Indonesia: A Socio-Anthropological Perspective - Yazwardi, Yazwardi; -, sandy wijaya; Erniwati, Erniwati (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2025)
Religious moderation has become a critical policy discourse in Indonesia to mitigate escalating interreligious tensions and maintain social cohesion in a diverse society. Nonetheless, although moderation is extensively advocated at moral and institutional levels, its connection to legal pluralism, especially in influencing individuals' legal consciousness within a plural legal framework, remains inadequately examined. This study seeks to analyse the comprehension and negotiation of religious moderation by religious leaders in the context of legal pluralism, and how this interplay mirrors wider trends of plural governance in modern Indonesia. The study utilised a quantitative design supplemented by minimal qualitative insights, gathering data using a structured questionnaire administered to sixty religious leaders associated with prominent religious organisations in Palembang, a diverse urban environment in South Sumatra. The findings indicate a notable epistemic asymmetry: respondents exhibit a high level of understanding of religious moderation, yet their grasp of legal pluralism is relatively inferior, highlighting a disparity between normative acceptance of tolerance and practical awareness of plural legal systems. This study theoretically adds by introducing the idea of legal consciousness to connect religious moderation with legal pluralism, emphasising that symbolic acceptance of coexistence does not inherently equate to support for plural legal governance. The findings indicate the necessity for policy initiatives that incorporate legal education, civic reasoning, and interreligious dialogue to enhance inclusive governance at the local level. This study contextualises Indonesia within wider discussions on post-secularism and legal pluralism in the Global South, providing fresh perspectives on the difficulties of reconciling religious values with democratic legal systems in diverse nations.